PENGEMBANGAN KUNCI DETERMINASI TUMBUHAN HASIL EKSPLORASI HUTAN WISATA GUCI KABUPATEN TEGAL UNTUK SEKOLAH MENENGAH ATAS - Izza, Fika Rofiuddin; Retnoningsih, Amin; Pukan, Krispinus Kedati (Badan Pengembang Konservasi UNNES, 2018)
Classification of living things is one of Biology material in the senior high school level which explains the formation of various animal and plants groups until structured the taxon following a hierarchy. The identification process of living things especially plants is one of activities that need students’ accuracy through observation. The plants identification process with determination key is main discussion on plants classification material in Biology learning for tenth grade of senior high school students. The problems found in living things classification material (plants) are difficulty in recognizing the plants characteristics, less key determination media, and lesson plan arranged by teacher tends only to be used for classroom activity. Furthermore, learning media is needed for increasing students’ competency from nature exploration which is used for identifying school’s environment. Plants key determination media which is developed from exploration of Guci forest tourism in Tegal Regency. Analysis of exploration result is 32 family and 50 species of plants are identified. The key determination media is validated by material expert with very valid result by score 85.7% and 94.4% from media expert. The media implementation in the learning results students’ score achievement by more than 93.9% students’ score surpassed KKM (minimum completeness criteria) with very good response from students and teacher while the method applied in the learning in the senior high school.